Business Interest versus Consumer Protection. Conflicts within the Safety Assurance System of NonFood Products – Selected Issues - Żywicka, Agnieszka (Review of European and Comparative Law, 2023)
Technological progress and the introduction of more and more new products to the market have intensified the process of changes in EU and national law within the product safety system. Legislative activities aimed at intensifying consumer protection have been observed in this area for several years. The primary role of instruments and legal mechanisms under this system is currently to guarantee consumer protection (protection of health and life) against the risks generated by various new products introduced to the market. In this respect, public law institutions adopted in this system play the leading role. These include market control and surveillance, product monitoring, and a coordinated system of informing about dangerous products.